Perilaku Wakif dalam Mewakafkan Tanahnya untuk Kesejahteraan Masyarakat di Kecamatan Kediri Kabupaten Lombok Barat - Ahmad Muzayyan Haqqy; Busaini Busaini; Ihsan Rois (IQTISHODUNA: Jurnal Ekonomi Islam, 2017)
Donations of land is one of the instruments in the Islamic economy for the welfare of the people. In this study, explained that people in Kediri, West Lombok regency have a high motivation to benefact although many people are under the poverty line. This happens because the benefactor in Kediri understood donations of land for the provision of the reward in the hereafter will continue to flow because it is used to build educational facilities and mosques as a means of worship for the wider community. Utilization of donations of land for public welfare in the district of Kediri aims to (1). Eliminating ignorance and educate the people to build education facilities, (2). Reducing poverty and open up employment opportunities, (3). Eliminating social inequalities with the participation of most of the people managing the benefaction land.